Relationship between mega-scale glacial lineations and iceberg ploughmarks on the Bjørnøyrenna Palaeo-Ice Stream bed, Barents Sea - Andreassen, Karin; Piasecka, Emilia D.; Stokes, Chris R.; Winsborrow, Monica C.M. (Marine Geology, 2018)
Submitted manuscript version: Published version available in Relationship between mega-scale glacial lineations and iceberg ploughmarks on the Bjørnøyrenna Palaeo-Ice Stream bed, Barents Sea (2017). Mega-scale glacial lineations (MSGLs) are ridge-groove corrugations aligned in the direction of the former ice flow, tens of kilometers long and up to a few hundred meters wide. They are the most striking subglacial features on the beds of former ice streams and play an important role in modulating ice flow through their influence on bed roughness and subglacial hydrology. Despite the importance of MSGLs, their formation remains enigmatic. Most studies have tended to focus on assemblages of MSGLs and their relationship to other landforms up-ice (e.g. drumlins or bedrock features in ice stream onset zones) but fewer studies have examined their characteristics and transition to other landforms towards ice stream grounding lines. In this paper, we investigate the relationship between an assemblage of MSGLs and ploughmarks on the bed of the former Bjørnøyrenna Ice Stream in the SW Barents Sea, which occurs in the central part of the ice streambed. A sample of MSGLs is used to test their potential origin, based on their metrics (width, length) and diagnostic characteristics predicted by formation theories. Results show a down-flow depth decrease of the MSGL grooves, and a shallowing tendency once they transition into ploughmarks. Their width shows an increasing tendency, which we link mostly to the strong divergence of the trough (and ice flow) downstream. The prominent continuity from linear to curvilinear features demonstrates that the grooves associated with MSGLs transition into icebergploughmarks. This observation is consistent with the hypothesis that the MSGLs have formed through a mechanism of “groove-ploughing”, at least in part. The continuity from MSGLs to iceberg ploughmarks resulted from detachment of large icebergs from the grounded ice wall or grounded ice shelf and their ploughing away from the ice ...